Processing of Industrial Metallurgical Wastes as the Basis of Manufacturing Technology Welding Fluxes and Additives NIM1; Key Engineering Materials; Vol. 736 : Materials and their Application - Kozyrev N. A.; Kryukov R. E.; Kozyreva O. A.; Gizatulin R. A. Rinat Akramovich; Valueva A. V. Anna Vladimirovna (2017, 2017)
Title screen